Larvicidal Activity and Midgut Histopathological Effects of Urena lobata Leaf Extract on Aedes aegypti - Ngurah Intan Wiratmini; Ni Made Suartini; Firman Andani; Tiffany Angelita Putri Mileva; Ni Wayan Bogoriani; Made Pharmawati (Bogor Agricultural University, Indonesia, 2026)
The use of chemical larvicides to control Aedes aegypti mosquito populations poses significant environmental risks. As an alternative, researchers are investigating plant-derived natural larvicides, which are biodegradable and safe for humans and non-target organisms. Urena lobata leaf extract has demonstrated biolarvicidal effect by causing larval mortality and morphological changes. This study evaluated the efficacy of U. lobata leaf extract against Ae. Aedes aegypti larvae, their effects on midgut histopathology, and their bioactive compounds were identified by liquid chromatography-mass spectrometry (LC-MS). A post-test control design was implemented with extract concentrations of 0.3%, 0.5%, 0.7%, and 0% (control), each replicated six times using 20 larvae per treatment. Mortality of third-instar larvae increased with higher extract concentrations. The lethal concentration (LC50) of U. lobata extract is 0.5% with a 95% confidence interval of 0.484-0.566. Histopathological analysis revealed structural damage in the midgut, including epithelial disorganization, vacuolization, swelling, and detachment of epithelial cells, loss of microvilli, and an irregular peritrophic membrane. Semi-quantitative histopathological scoring indicated that the 0.7% extract produced the most severe alterations. The bioactive compounds identified in the extract include flavonoids, saponins, triterpenoids, and tannins. In conclusion, these findings indicate that U. lobata leaf extract exhibits potential larvicidal activity targeting the midgut of Ae. aegypti larvae.